(untitled) (IASH Indian Journal of Arid Horticulture, 2024)
Sapota (Manilkara achras) is a tropical fruit tree that grows slowly and is evergreen. When fully mature, it is commonly eaten as a dessert fruit and is grown commercially in several countries, including India, Sri Lanka, the Philippines, Venezuela, and Mexico. However, because of its short shelf life and highly perishable nature, sapota has limited availability in the market. The main challenge in post harvest management of sapota is its quick ripening, which significantly reduces its shelf life. To address this issue, various techniques and technologies have been explored, such as the use of chemicals, plant growth regulators (PGRs), packaging materials, wax coating, and irradiation. This review aims to explore post-harvest solutions that can increase the availability of sapota fruits in the market for longer periods and maintain their quality throughout storage by extending their shelf life. By improving the shelf life of sapota through pre-harvest treatment and various storage applications, this study seeks to reduce post-harvest losses, increase availability, and ensure the economic sustainability of this horticultural crop.